Cardiovascular Disease Among Persons Living With HIV: New Insights Into Pathogenesis and Clinical Manifestations in a Global Context. Issue 1 (3rd January 2023) - Ntsekhe, Mpiko; Baker, Jason V.
Abstract : Widespread use of contemporary antiretroviral therapy globally has transformed HIV disease into a chronic illness associated with excess risk for disorders of the heart and circulatory system. Current clinical care and research has focused on improving HIV-related cardiovascular disease outcomes, survival, and quality of life. In high-income countries, emphasis on prevention of atherosclerotic coronary artery disease over the past decade, including aggressive management of traditional risk factors and earlier initiation of antiretroviral therapy, has reduced risk for myocardial infarction among persons living with human immunodeficiency virus-1 infection. Still, across the globe, persons living with human immunodeficiency virus-1 infection on effective antiretroviral therapy treatment remain at increased risk for ischemic outcomes such as myocardial infarction and stroke relative to the persons without HIV. Unique features of HIV-related cardiovascular disease, in part, include the pathogenesis of coronary disease characterized by remodeling ectasia and unusual plaque morphology, the relative high proportion of type 2 myocardial infarction events, abnormalities of the aorta such as aneurysms and diffuse aortic inflammation, and HIV cerebrovasculopathy as a contributor to stroke risk. Literature over the past decade has also reflected a shift in the profile and prevalence of HIV-associated heart failure, with a reduced but persistent risk of heart failure with reduced ejection fraction and a growing risk of heart failure with preserved ejection fraction. Cardiac magnetic resonance imaging and autopsy data have emphasized the central importance of intramyocardial fibrosis for the pathogenesis of both heart failure with preserved ejection fraction and the increase in risk of sudden cardiac death. Still, more research is needed to better characterize the underlying mechanisms and clinical phenotype of HIV-associated myocardial disease in the current era. Across the different cardiovascular disease manifestations, a common pathogenic feature is that HIV-associated inflammation working through different mechanisms may amplify underlying pathology because of traditional risk and other host factors. The prevalence and phenotype of individual cardiovascular disease manifestations is ultimately influenced by the degree of injury from HIV disease combined with the profile of underlying cardiometabolic factors, both of which may differ substantially by region globally.